The Role of a Condominium’s Association in Adapting, Complying, and Self-Reducing Anxiety in Response to COVID-19 Precautionary Measures - Fucà, Romina; Cubico, Serena; Leitão, João (Frontiers in Law, 2022)
Our article is part of a micro-inquiry into the small reality of co-ownership to formulate hypotheses on the evaluation of behaviors (non-pharmaceutical precautionary measures) in addition to pharmaceutical actions put in place by the authorities against future pandemics. Our article takes its first steps in the fact that one of the most common ways to fight the COVID-19 virus is to avoid close contact between people. Indeed, our condominium meetings have been canceled at the first COVID-19 vague (in late February 2020), and social distancing as well as the use of masks and hand sanitizer in the concierge are measures still adopted at the end of 2022. External people (parents, visitors in general, and patients from the three health offices housed in the condominium) have been reduced, and certain businesses, such as bed and breakfasts, which were operating until 2019, had been closed following the first vague of COVID-19 pandemics. The general condominium association has been centralized under the conscious direction of the doorman led by the administrator of the condominium and a support lawyer. Stray animals at the foot of the condominium and fed by a couple of residents have been reduced to the strict minimum. On a sample of 39 people questioned and from an age range between 17 and 93 years, actually residing in the condominium and excluding those members of families who do not actually reside there, we inquired how the risk of COVID-19 infection has decreased over the past year (December 2021-December 2022). The useful variables to determine the correlations between the precautionary behaviors adopted by the co-owners and a possible reduction in the risk of infection are: 1) size of the family (self-observed); 2) level of education (self-observed); 3) professional status (self-observed); 4) salary (self-observed); 5) travel history (self-observed); 6) annual charity (self-observed estimate); 7) confidence in sustainability (interviews via mobile chat); 8) doses of vaccines already taken to the time of the survey (interviews via mobile chat); and 9) depressive symptoms (interviews via mobile chat). Our survey targets to highlight how residents’ safety in the case of one of the most recent periods of COVID-19 pandemics—i. e. the starting winter season 2022‒2023—is somehow safeguarded by cooperative games because of condominiums rules’ fulfillment as well as by socio-juridical precautionary measures taken by the ruling association.